IMPLEMENTASI WEBSITE COMPANY PROFILE DAN PERSURATAN SEBAGAI INOVASI TEKNOLOGI DIGITAL DESA KARYA MAKMUR - Juniawan, Fransiskus Panca; Assobry, Muhammad Habib; Megawati, Megawati; Syahputra, Razen; Ali, Firman; Nayla, Adinda; Carissa, Fihan; Sylfania, Dwi Yuny (Universitas Islam Malang, 2025)
Karya Makmur Village is one of the villages in Bangka Belitung province located in Bangka Regency. Like most other villages, this village has problems with correspondence services, likely still manually. In addition, there is a lack of information that can be collected regarding village programs and business opportunities. The goal of this activity is to implement a web-based correspondence sistem and a village information website that can be displayed on smart TVs to improve management efficiency and data transparency. Residents can submit letters online, and village officials can speed up the processing of these correspondences while smart TVs display public information in real-time. This activity uses the service learning method in its implementation which consists of five stages, namely socialization, needs identification, system implementation, user training, and evaluation. This method was chosen because of its advantages in involving students so they can directly feel the experience of sharing skills and knowledge to the community so that they feel like better people. The results of the implementation show that the service is faster and more accurate, and the processing time for letters has been significantly reduced. The use of smart TVs increases the transparency of the budget and development programs and increases residents' access to village information. The training successfully addresses infrastructure and digital literacy issues. Overall, digitalization helps build more effective villages with more people participating.